Genetic Relatedness and Superantigen Expression in Group A Streptococcus Serotype M1 Isolates from Patients with Severe and Nonsevere Invasive Diseases - Chatellier, Sonia (American Society for Microbiology, 2000)
The relatedness of group A streptococcal (GAS) strains isolated from 35 Canadian patients with invasive disease of different severity was investigated by a variety of molecular methods. All patients were infected with M1T1 strains and, based on clinical criteria, were classified as severe (n = 21) and nonsevere (n = 14) invasive GAS infection cases. All the M1 strains studied had the emm1.0 allele and the same streptococcal pyrogenic exotoxin (Spe) genotype, speA(+) speB(+) speC speF(+) speG(+) speH smeZ(+) ssa. All isolates had the same speA allotype, speA2. The randomly amplified polymorphic DNA banding pattern with two different primers was identical for all strains, and pulsed field gel electrophoresis analysis showed that 33 and 30 isolates had identical banding patterns after DNA digestion with SfiI or SmaI, respectively; the nonidentical isolates differed from the main pattern by only one band. A relatively high degree of polymorphism in specific regions of the sic gene was observed among isolates; however, this polymorphism was not associated with disease severity. Likewise, although the phenotypic expression of SpeA, SpeB, and SpeF proteins varied among the M1T1 isolates, there was no correlation between the amount of Spe expressed and disease severity. Importantly, mitogenic and cytokine responses induced by partially purified bacterial culture supernatants containing a mixture of expressed superantigens were very similar for isolates from severe and nonsevere cases (P > 0.1). Together, the data indicate that highly related invasive M1T1 isolates, some indistinguishable, can cause disease of varying severity in different individuals. These findings underscore the contribution of host factors to the outcome of invasive GAS infections.